Simulations of High-order Nonlinear Optical Spectra on Polymers of Three-level Systems - Berger-Malette, Grégoire Zachary Aubert Laurier (Université d'Ottawa / University of Ottawa, 2023)
This thesis describes the computational tools that allow the simulation of polymers made up of an arbitrary number of three-level systems, the study of such systems and comparisons to experimental nonlinear optical spectra. The three-level system generator (3LSG), is designed to automatically generate the operators that describe the system, whether it is a closed system or an open quantum system (OQS) in contact with a bath, with just a few input parameters. A user is free to specify each 3LS's energy levels and transition dipoles between said levels, site couplings between the different units of the polymer and in the case of open systems, the rates and couplings describing the different relaxation processes taking place in an OQS, using the Redfield formalism. In either cases, the 3LSG is then capable of generating the Hamiltonian 𝐻₀ describing the closed system or the Liouvillian 𝓛₀ describing the open system from the various inputs. The Ultrafast Spectroscopy Suite (UFSS) is an open-source software suite used to perform the nonlinear optical spectroscopies simulations. It contains 4 main modules, one of which is the Hamiltonian/Liouvillian Generator (HLG), a module previously designed to model simpler two-level systems. The 3LSG is a sub-module of the HLG. The three-level system generator is used to replicate a theoretical model describing a copolymer model made of many identical pairs of squaraine monomers, where each monomer is a three-level system interacting with its neighbouring sites and a surrounding bath. The system automatically generated by the 3LSG is used, along with other spectroscopic calculation tools, to simulate high-order transient absorption (TA) spectroscopies and study the long-time behaviour of the 3rd-order to 13th-order excited state absorption (ESA) peaks in the TA signals. The 3LSG is used in conjunction with spectroscopic calculations tools as it was originally intented, though it may also be used by itself to study Hamiltonians and Liouvillians of electronic three-level systems.
Keywords: nonlinear optical spectroscopy; computational physics